Differential Effect of Diazepam in Unstressed and Stressed Mice - Anki Tyagi, Vaibhav Walia (Journal of Applied Pharmaceutical Science, 2017)
Aim: Investigation of antidepressants like effect of diazepam in unstressed and stressed mice.Materials and methods: Male Swiss albino mice were used in the present study. Mice were stressed by immobilization for 2h. Mice subjected to immobilization were considered as stressed mice and mice not subjected to immobilization were considered as unstressed mice. Depression like behavioral alterations in unstressed and stressed mice was measured by tail suspension test (TST) followed by forced swim test (FST).Results: The present study showed that the immobilization stress of 2h significantly enhanced the immobility period of mice in both TST and FST. Fluoxetine (FLX) (20 mg/kg, i.p.) significantly reduced the immobility period of both unstressed and stressed mice significantly as compared to their respective controls. Diazepam (DZP) (2 mg/kg, i.p.) significantly increased the immobility period of the unstressed mice whereas significantly reduced the immobility period of stressed mice in both TST and FST as compared to their respective controls. Administration of DZP (2 mg/kg, i.p.) and FLX (20 mg/kg, i.p.) to the unstressed mice reduced the immobility period of unstressed mice in both TST and FST significantly as compared to the vehicle and DZP (2 mg/kg, i.p.) treated unstressed mice in TST. The co-administration of DZP (2 mg/kg, i.p.) and FLX (20 mg/kg, i.p.) after the immobilization of 2h significantly reduced the immobility period of stressed mice significantly as compared to the vehicle treated stressed mice in both TST and FST.Conclusion: It is concluded that the administration of DZP (2 mg/kg, i.p.) to the stressed mice reduced the immobility period of stressed mice in both TST and FST. Thus DZP (2 mg/kg, i.p.) exerted the antidepressants like effect in the stressed mice.
Keywords: Depression, diazepam, fluoxetine, mice, stress.